Pacing profile and performance of under 23 and elite mountain bikers during cross-country short track event - Arriel, R. A.; Meireles, A.; Souza, H.; Marocolo, M. (Journal of Science and Cycling, 2023)
The aim of this study was to investigate the distribution of speed and performance of professional cross-country cyclists on different technical and non-technical sections during a cross-country short track (XCC) mountain biking (MTB) event. Twenty male professional cross-country cyclists (25.9 ± 5.4 years) performed six laps of an XCC International Mountain Bike Cup. In addition to categories [Under 23 (n = 8) and Elite (n = 12)], cyclists were divided into three groups according to their overall race completion time, being categorized as top (n = 6), middle (n = 8) and bottom (n = 6) placed finishers (race time groups). Average speed (by lap and in five different track sections) was analyzed according to all athletes, categories and race time group. Athletes in general and both categories adopted a positive pacing. Top cyclists adopted a "W-shaped" pacing, while middle and bottom cyclists adopted a positive and parabolic-shaped pacing profile, respectively. Regarding track sections performance, no difference was found between categories (p > 0.05). Nevertheless, top cyclists were 18.8% (p < 0.05), 6.7% (p < 0.05) and 4.1% (p < 0.05) faster than bottom cyclists on sustained non-technical uphill, technical short uphill/downhill section and non-technical downhill sections of the track, respectively. The results show that majority of athletes adopted a positive pacing profile for the analyzed circuit, but the better XCC performance was associated with a "W-shaped" pacing profile and higher performance mainly on sustained non-technical uphill.